2015
DOI: 10.1002/nme.4983
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale seamless‐domain method for linear elastic analysis of heterogeneous materials

Abstract: SUMMARYA multiscale numerical technique, termed the seamless-domain method (SDM), is applied to linear elastic problems. The SDM consists of two steps. The first step is a microscopic analysis of the local simulated domain to construct interpolation functions for discretizing governing equations. This allows an SDM solution to represent a structure consisting of heterogeneous microstructure(s) without homogenization. The second step is a macroscopic analysis of a seamless global (entire) domain that has only c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Previous manuscripts demonstrated that the SDM multiscale numerical technique, can accurately solve linear steady-state heat conduction (Suzuki and Soga, 2016) and elasticity (Suzuki, 2016a(Suzuki, , 2016b problems. This study presented a simple nonlinear solver for the SDM analysis of heterogeneous materials, and investigated the practicalities of applying the SDM scheme to nonlinear stationary temperature fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous manuscripts demonstrated that the SDM multiscale numerical technique, can accurately solve linear steady-state heat conduction (Suzuki and Soga, 2016) and elasticity (Suzuki, 2016a(Suzuki, , 2016b problems. This study presented a simple nonlinear solver for the SDM analysis of heterogeneous materials, and investigated the practicalities of applying the SDM scheme to nonlinear stationary temperature fields.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work (Suzuki and Soga, 2016, Suzuki, 2016a, 2016b, a multiscale analysis called the seamless-domain method (SDM) was developed and applied to linear analyses. When conducting a macroscopic analysis of an entire field, the SDM constructs a meshfree model that is represented by only a small number of coarse-grained points (CPs).…”
Section: Introductionmentioning
confidence: 99%
“…By giving enforced-displacement boundary conditions ( 1 u and 4 u ) and solving the below simultaneous equations, we can obtain unknown displacements ( 2 u and 3 u ). (Suzuki and Soga, 2016;Suzuki, 2016a;Suzuki, 2016b). Suzuki, Mechanical Engineering Journal, Vol.4, No.4 (2017) [DOI: 10.1299/mej.…”
Section: L-shaped Beammentioning
confidence: 99%
“…The detailed formulations are presented in subsection 3.3.2. The different features of the SDM in itself compared to other numerical solvers were illustrated in (Suzuki and Soga, 2016;Suzuki, 2016a).…”
Section: Differences Compared With the Standard Super-elementsmentioning
confidence: 99%
See 1 more Smart Citation